Financial literature and nationalism in intention In Share Investor Prospective Millenial Generation - Fitri Fitri; Dewi Anggraeni; Nurwahidah Mashuddin; Nulaela (Enrichment : Journal of Management, 2022)
The tendency of increasing stock investment among millennials indicates they are literate in financial literacy. Then, state-owned companies become an attraction for potential investors because they are considered to have promising profit prospects, as well as security in investing. This study aims to analyze the effect of financial literacy on the intention to invest in shares of potential investors among the millennial generation and the influence of nationalism as a mediator. This study uses a survey method with a quantitative approach. We have distributed questionnaires to 250 respondents who are millennials born after the 1980s. Field data were then analyzed using multiregression analysis techniques. We find that financial literacy has a significant effect on investors' intention to buy shares of State-Owned Enterprises (BUMN). Nationalism can also strengthen the relationship of financial literacy with investors' intentions to buy shares of state-owned companies.